The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/drones5040117
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Leak Detection and Quantification of Methane Emissions Using sUAS

Abstract: Detecting and quantifying methane emissions is gaining an increasingly vital role in mitigating emissions for the oil and gas industry through early detection and repair and will aide our understanding of how emissions in natural ecosystems are playing a role in the global carbon cycle and its impact on the climate. Traditional methods of measuring and quantifying emissions utilize chamber methods, bagging individual equipment, or require the release of a tracer gas. Advanced leak detection techniques have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 158 publications
(206 reference statements)
0
6
0
Order By: Relevance
“…However, monitoring the entire production, transmission, and/or distribution system with stationary sensors requires a large quantity of sensors. Furthermore, sensors close to the ground may fail to detect leaks when heat and wind disperse the gas to higher altitudes, being out of reach of sensors [14], [35]. For such reasons, stationary sensor solutions are typically deployed close to gas production facilities or high risk areas [5], [28].…”
Section: A Array Of Stationary Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, monitoring the entire production, transmission, and/or distribution system with stationary sensors requires a large quantity of sensors. Furthermore, sensors close to the ground may fail to detect leaks when heat and wind disperse the gas to higher altitudes, being out of reach of sensors [14], [35]. For such reasons, stationary sensor solutions are typically deployed close to gas production facilities or high risk areas [5], [28].…”
Section: A Array Of Stationary Sensorsmentioning
confidence: 99%
“…UAVs allow lower flying altitudes (e.g. Class G airspace not available to manned aircraft [14]) and authors have reported the ability to detect with LIDAR sensors leak rates as low as 5 kg/hr when flying the UAV at altitudes ranging from 3m to 15m above the leak [53] and 13 kg/hr when flying at an altitude of 50m [31].…”
Section: ) Remote Airborne Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…5d). 112,132,[166][167][168][169] Black box artificial neural networks without a physical atmospheric model have also successfully localized the emissions for gases from data collected with an array of sensors. 170,171 These methods have been applied for methane emissions monitoring but are expected to be applicable for hydrogen or hydrogen-methane blends as well.…”
Section: Hydrogen As An Interfering Gasmentioning
confidence: 99%
“…33,34 Combining ML algorithms with unmanned aerial and ground vehicles has also been shown as a promising method to survey natural gas infrastructure for leaks where large areas in remote locations need to be covered. [35][36][37] Other surveys have compared different machine learning techniques z E-mail: lktsui@unm.edu ECS Sensors Plus, 2023 2 011402 applied to other types of gas sensors 38,39 and specific studies such as Tsitron et al 40 demonstrate the application of a single machine learning technique such as Bayesian decoding to MPES devices. We have previously demonstrated the effectiveness of artificial neural networks for gas mixture identification in the context of natural gas emissions 18 and automotive emissions.…”
mentioning
confidence: 99%